"Nilai-Nilai Dakwah dalam Interaksi Psikologi Keagamaan Guru Diaspora Indonesia terhadap Siswa di Sangkhom Islam Wittaya School, Thailand" - Qudratullah, Qudratullah (Jurnal Dakwah Tabligh, 2024)
This study aims to examine the internalization of da'wah values in the religious psychological interaction between Indonesian diaspora teachers and students at Sangkhom Islam Wittaya School, Thailand. Employing a descriptive qualitative approach, data were collected through in-depth interviews, participatory observation, and documentation, and subsequently analyzed using the interactive analysis model developed by Miles, Huberman, and Saldaña. The findings reveal that the values of compassion (mawaddah) and exemplary conduct (uswah hasanah) serve as the main foundations in religious interactions. Compassion is manifested through attention, empathy, and support for students' academic and spiritual development, creating a safe space for the exploration of religious identity. Meanwhile, teachers’ exemplary behavior in daily life authentically reinforces the internalization of Islamic values within the students. This interaction not only serves as a means of knowledge transfer but also acts as a medium for the formation of students' moral character and Islamic identity. This study contributes to the development of cross-cultural da'wah communication theory and enriches the field of Islamic educational psychology studies in the context of Muslim minority settings